FORECASTING OF COMMERCIAL FISH (BELONIFORMES:ORDER) CATCH IN CHILIKA LAGOON, ODISHA, INDIA - RAMAN, R K; SAHOO, A K; MOHANTY, S K; DAS, B K (Journal of the Inland Fisheries Society of India, 2021)
Beloniformes is a commercial fish with abundant species of (Strongylura strongylura and Hyporhamphus limbatus) recorded in Chilika lagoon, India. In the present study, two SARIMA (Seasonal Auto Regressive Integrated Moving Average) and SARIMAX (SARIMA with external regressors) models were developed on the monthly time series in Chilika lagoon data for the period 2001-02 to 2015-16 and forecasted up to 2017-18. The goodness of fit criteria such as Akaike Information Criteria (AIC), Bayesian Information Criterion (SBC) and R2 were used for model performances. SARIMAX model was developed using SARIMA (1,0,0)(1,0,0)12 with physicochemical factors; factor1, factor2, factor3 and factor4 to correlate the physicochemical parameters with catch in the lagoon. Here factor1 is the combined effect of salinity, temperature, pH and dissolve oxygen, factor2 dominated by pH and salinity, factor3 dominated by dissolve oxygen and factor4 dominated by temperature. SARIMAX model (SARIMA (1,0,0)(1,0,0)12 with regressor factor1) found the best fitted model. The model predicted that an increase of 10% per year (SARIMA) and an increase in 16% per year (SARIMAX) with respect to base year 2015-16 in the total beloniformes catch in the lagoon for the period 2016- 17 and 2017-18 by maintaining the present environmental condition.Key words: Chilika, beloniformes, SARIMA, SARIMAX model, forecasting